The Influence of Social Media Marketing Activities on Purchase Intention Through Brand Trust and Brand Image - Abdullah B, Muhammad; Yulianto, Edy; Fahrudi, Agung Nugroho Luthfi Imam (Sekolah Pascasarjana Universitas Brawijaya, 2025)
The rapid growth of social media platforms has transformed marketing strategies, especially within Indonesia's fast-moving consumer goods (FMCG) sector. Social media marketing activities (SMMA) have become vital for influencing consumer behavior, particularly on Instagram. This research aims to investigate the effect of SMMA on purchase intention, with a specific focus on the mediating roles of brand trust and brand image. A quantitative explanatory research design was employed, utilizing Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. Data were collected from 175 active followers of Fore Coffee’s Instagram account, ensuring the sample represented engaged consumers within the FMCG sector. The results reveal that SMMA positively impacts purchase intention both directly and indirectly. The mediating variables, brand trust, and brand image, significantly strengthened the relationship between SMMA and purchase intention. These findings underscore the importance of well-crafted social media marketing strategies in enhancing consumer purchase intention, building stronger brand trust, and fostering a favorable brand image. The study concludes that businesses within competitive industries, such as the FMCG sector, should prioritize effective social media marketing to drive consumer engagement and establish lasting customer relationships.Keywords: social media marketing, purchase intention, brand trust, brand image, fast-moving consumer goods